P-013 Testicular spermatozoa for intra-cytoplasmic sperm injection after IVF failure with ejaculated spermatozoa: a propensity score-matched cohort study. (30th June 2022) - Benchaib, M; Soignon, G; Labrune, E; Jaeger, P; Jovet, C; d'Estaing, S. Giscard; Lornage, J; Salle, B
Abstract: Study question: Does the use of testicular spermatozoa from non-azoospermic infertile men after failed IVF with ejaculated spermatozoa increases the pregnancy rate? Summary answer: Depending on semen characteristics and obtained embryos number at the previous IVF failure with ejaculated spermatozoa, it seems licit to propose ICSI with testicular spermatozoa. What is known already: Ejaculated spermatozoa are generally considered to possess better fertilisation potential than testicular spermatozoa as their maturation has been completed. However, it has been shown that in selected cases, the use of testicular spermatozoa from non-azoospermic infertile men resulted in a higher implantation and pregnancy rate than the use of ejaculated spermatozoa. One of the reasons for this result is a higher DNA fragmentation index (DFI) in ejaculated spermatozoa compared to testicular spermatozoa. This increase in DFI would negatively affect embryo development and implantation. Study design, size, duration: A retrospective matched cohort study using propensity score matching (PSM) analysis was performed. After an IFV failure (cycle_1), IVF with ejaculated or testicular spermatozoa was performed (cycle_2). Female age, female BMI, IVF rank, stimulation protocol, gonadotropin total quantity, treatment duration, punctured oocytes number, and mature oocytes punctured were included in PSM. The matching was performed for IVF performed in cycle_1 for cases and controls identified in cycle_2. 26 couples were included between 01/01/2012 and 30/09/2021. Participants/materials, setting, methods: Among the 126 couples, for 63 couples, the cycle_2 was performed with ejaculated spermatozoa (controls) and for 63 couples with testicular spermatozoa (cases). Mixed logistic regression was used to compare outcomes of cases versus controls groups. The cycle_1 have allowed finding the prognostic factors to propose a cycle_2 ICSI with testicular spermatozoa in case of cycle_1 IVF failure. The study outcomes were the pregnancy rate (PR) and the cumulative pregnancy rate (CPR). Main results and the role of chance: In cycle_1, no difference was observed for the parameters included in PSM. The DFI was higher in case group (13.7% ± 10.5% versus 9.3% ± 4.4%, p < 0.05), no difference was observed for fertilization rate, blastulation rate and frozen embryo rate. However, the PR was higher in case group (22.2% versus 0.0%, p < 0.001), the same result was found for the CPR (25.4% versus 6.3%, p < 0.001). The main prognostics factors to propose a cycle_2 ICSI with testicular spermatozoa after cycle_1 IVF failure with ejaculated spermatozoa: teratozoospermia or cryptozoospermia in cycle_1 (OR = 6.0 [1.2 ; 31.1], p < 0.05), a number of obtained embryos greater than 7 in cycle1 (OR = 5.3 [1.5 ; 18.0], p < 0.01), independently of male age in cycle_1 (OR = 2.3 [0.8 ; 6.5], p > 0.05 Limitations, reasons for caution: The main limitations of the current study is being retrospective rather than prospective randomized. However, the used of the propensity score to perform a case-control study allow this study to be more reliable and to obtain results corresponding to real life. Wider implications of the findings: This study is in favour of using testicular spermatozoa after IVF failure with ejaculated spermatozoa when the semen morphology is altered or in case of cryptozoospermia, and when at least 8 embryos was obtained in the previous IVF procedure Trial registration number: not applicable